Antioxidant and cytoprotective activities of piper betle, Areca catechu, Uncaria gambir and betel quid with and without calcium hydroxide - Sazwi, N.N.; Nalina, T.; Rahim, Z.H.A. (BioMed Central, 2013)

(untitled)
Background: Betel quid chewing is a popular habit in Southeast Asia. It is believed that chewing betel quid could reduce stress, strengthen teeth and maintain oral hygiene. The aim of this study was to investigate the antioxidant and cytoprotective activities of each of the ingredients of betel quid and compared with betel quid itself (with and without calcium hydroxide). The correlation of their cytoprotective and antioxidant activities with phenolic content was also determined.